Critical Encounters with Habermas's Political and Legal Theory - Abromeit, John; Dimick, Matthew; Linden-Retek, Paul (Social Sciences E-Books Online, Collection 2026., 2026)
With over a dozen contributions from scholars across a range of disciplines, this book revisits Jürgen Habermas's defining text on legal and political theory, Between Facts and Norms (1992). The contributors interrogate the prospects for Habermas's optimistic defense of liberal democracy in our current age of straining global capitalism and menacing authoritarian populisms. The authors arrive at different conclusions, with some contributors engaging directly with his theory while others assessing it through the prisms of political economy, the media, policing, employment discrimination law, international relations theory, social movements, democratic institutions and the historical context of Between Facts and Norms .